The 400- and 800-m track running induces inspiratory muscle fatigue in trained female middle-distance runners - Ohya, T.; Yamanaka, R.; Hagiwara, M.; Oriishi, M.; Suzuki, Y. (The Journal of Strength and Conditioning Research, 2016)
Inspiratory muscle fatigue (IMF) may limit exercise performance. A few studies have reported that IMF occurs after short-duration swimming exercise, but whether short-duration running can induce IMF remains unclear. Intra-abdominal pressure is increased during running through diaphragmatic activation to stabilize the spine during movements of the upper limbs. This occurs along with the increased inspiratory muscle effort associated with increased respirations during exercise; thus, we hypothesized that short-duration running exercise would induce IMF. To test this hypothesis, we measured maximal inspiratory pressure (MIP) before and after 400- and 800-m track running sessions. Eight female middle-distance (400, 800 m) runners performed a 400- and 800-m running test. Maximal inspiratory pressure was measured before and after each test using a portable autospirometer. The mean MIPs were significantly lower after running than before running; values obtained were 107 ± 25 vs. 97 ± 27 cmH2O (p = 0.01, effect size [ES] = 0.65) and 108 ± 26 vs. 92 ± 27 cmH2O (p = 0.01, ES = 0.74) before vs. after the 400- and 800-m tests, respectively. The mean MIP after the 800-m test was significantly lower than after the 400-m test (p = 0.04, ES = 0.48). There was no correlation between IMF value and running time (r = 0.53 and r = -0.28 for either the 400- and 800-m tests, respectively; p > 0.05). In conclusion, IMF occurs after short-duration running exercise. Coaches could consider prescribing inspiratory muscle training or warm-up in an effort to reduce the inevitable IMF associated with maximal effort running.